RETRACTED: Assessment of 2-Pentadecyl-2-oxazoline Role on Lipopolysaccharide-Induced Inflammation on Early Stage Development of Zebrafish (Danio rerio) - Davide Di Paola; Sabrina Natale; Enrico Gugliandolo; Marika Cordaro; Rosalia Crupi; Rosalba Siracusa; Ramona D’Amico; Roberta Fusco; Daniela Impellizzeri; Salvatore Cuzzocrea; Nunziacarla Spanò; Fabio Marino; et al. (Life)
Lipopolysaccharide (LPS), or bacterial endotoxin, is an important virulence factor in several human and animal pathologies. Oxazoline of Palmitoylethanolamide (PEAOXA) has shown strong anti-inflammatory activity in several animal models. LPS was applied for 24 h to zebrafish embryos to induce inflammation, and then the anti-inflammatory action of PEAOXA was evaluated for the first time in the zebrafish model (Danio rerio). Different concentrations of PEAOXA were tested for toxicity on zebrafish embryonic development; only the highest concentration of 30 mg/L showed toxic effects. Quantitative RT-PCR was applied to detect Tumor necrosis factor-?, Interleukin 1?, 6, and 8, and members of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB). Exposure to LPS induced an increase in pro-inflammatory cytokines (tumor necrosis factor and interleukin 1, 6, and 8) in both gene and protein expression, as well as an increase of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) and the nuclear factor kappa light polypeptide enhancer in B-cells inhibitor (I?B?) gene expression. Furthermore, acute LPS exposure also induced an increase in tryptase release, related to mast cell activity, and in the production of apoptosis-related proteins (caspase 3, bax, and bcl-2). Treatment with PEAOXA 10 mg/L significantly counteracts LPS-induced inflammation in terms of cytokine expression and decreases tryptase release and the apoptosis pathway.